Job satisfaction and perceived stress among radiology technicians: a questionnaire survey in relation to sociodemographic and occupational risk factors - AKYURT, NURAN (SPRINGER, 2021)
Purpose To evaluate job satisfaction and perceived stress among radiology technicians in relation to sociodemographic and occupational risk factors. Methods A total of 207 radiology technicians were included in this questionnaire-based study. The questionnaire elicited items on sociodemographic and occupational characteristics along with Minnesota Satisfaction Questionnaire (MSQ) and Perceived Stress (PSS) scales to assess job satisfaction and the perceived stress, respectively. Results Multivariate analysis revealed that more years in practice (B: - 4.80, BCa 95% CI - 7.26 to - 2.47), being uncomfortable with working in a radiation environment (B: - 6.30, BCa 95% CI - 9.62 to - 2.61) and the use of public transport to get to work (B: - 3.62, BCa 95% CI - 6.53 to - 1.03) were significant predictors of poorer job satisfaction, whereas break time (B: 8.54, BCa 95% CI 4.63-12.14) and following scientific literature (B: 8.32, BCa 95% CI 3.37-12.89) significantly predicted the better job satisfaction. Being satisfied with the current job (p < 0.015) and high-income class (p = 0.005) were associated with lower perceived stress levels, while higher perceived stress level (B: - 0.48, BCa 95% CI - 0.66 to - 0.32) was also a significant predictor of poorer job satisfaction. Conclusion In conclusion, our findings revealed job satisfaction and perceived stress of radiology technicians to be at moderate levels and to be negatively correlated with each other. Our findings emphasize the importance of continuing education, in-service refresh training and continuing practice of regularly updating self-knowledge along with balance workload, income and safety at work to improve job satisfaction among radiology technicians.
Keywords: Radiology technicians; Job satisfaction; Perceived stress; Risk factors; Sociodemographic; Occupational